Training and Workplace Requirements: Strategies for Minimizing the Mismatch Gap - Wanyeki , Paul; Kisilu , Kitainge; Ferej , Ahmed (African Journal of Education,Science and Technology (AJEST), 2017)
The need for quality training offered by Technical and Vocational Education and Training (TVET) institutions and the production of graduates who meet the needs of the workplace has been growing in Kenya, Africa and internationally. Changing technology, competition and globalization have been cited as forces putting pressure on industry to rapidly evolve to ensure survivability. This study sought to investigate factors in institutions mitigating against closing the skills gap between what TVET institutions impart and what the modern workplace requires. Data was collected through survey method from trainers in TVET institutions in 17 Counties across Kenya. Selective interviews were also conducted in these institutions. The study found that indeed a mismatch or skills gap between what TVET offered and workplace requirements exists. The skills gap was attributed to several factors including, curriculum that was not regularly updated and with the participation of all relevant stakeholders; lack of adequate and competent and up to date instructors; insufficient teaching and learning facilities; inappropriate teaching and learning facilities, poor collaboration with training providers and the workplace; poorly supervised industrial attachment and an inappropriate attitude towards lifelong learning. A strong linkage between training institutions and the workplace was indicated as critical in reducing the skills gap. TVET instructors and Principals reported minimal contact with the workplace, with industrial attachment being the only point of convergence between the two. The study recommends that the TVET institutions should work diligently towards improving linkages in order to narrow the mismatch in skills gap.